Direct Surface-wave Tomography from Ambient Noise in the Shanxi Rift Zone and Adjacent Areas - Hao ZHANG; Jianshe LEI; Xiaoyan SONG; Yue DENG (CT Lilun yu yingyong yanjiu)
The Shanxi rift zone is one of the most active continental rift zones in the world. Obtaining a fine three-dimensionalS-wave velocity structure of the crust in this region helps understand the formation mechanism of continental rifts. In this study, continuous waveform data recorded at 113 fixed provincial stations deployed in Shanxi, Inner Mongolia, Hebei, Henan, and Shaanxi between January 2021 and December 2022 were utilized. A total of 4951 high-quality Rayleigh wave phase velocity dispersion curves in the 5~40 s period range were extracted. Using the direct surface wave imaging method, a three-dimensional S-wave velocity structure of the crust in the Shanxi rift zone and surrounding areas at depths of 0~40 km was obtained. The results show that the S-wave velocity structure at a depth of 5 km correlates with the distribution of surface fault zones and thickness of the sedimentary layers. Rift zones generally exhibit low-velocity anomalies with high-velocity anomalies on both sides of the uplift areas. As depth increases, the low-velocity anomaly gradually decreases, with low-velocity zones extending from the surface to approximately 15 km depth. At a depth of 25 km, the low-velocity anomalies in the central and southern parts of the Shanxi rift zone, including the Taiyuan, Linfen, and Yuncheng basins, transitioned from the upper crust to high-velocity anomalies in the lower crust, extending to the top of the upper mantle. This may have been caused by cooling of the basaltic magma intruding beneath the basins during the early Tertiary period before rifting. In the Datong volcanic region, the low-velocity anomaly extends from the top of the upper mantle to approximately 20 km depth in the crust and shifts from west to east, clearly revealing the magma upwelling pathway beneath Datong. A large low-velocity anomaly north of 38°N was inferred to have been caused by crustal heating and partial melting due to extensive volcanic activity in the Datong volcanic region since the Neogene. The high-resolution three-dimensional S-wave velocity structure of the crust obtained in this study provides valuable insights into the formation mechanisms of continental rifts.